Basic Principles And A Brief History Of The Organization Of Neurotraumatology Care For Patients With Acute Traumatic Brain Injury (Journal of Pharmaceutical Negative Results, 2023)
The organization of neurotraumatology care for victims with acute traumatic brain injury (TBI) is a system of measures for the prevention, diagnosis, conservative and surgical treatment and rehabilitation of patients with acute TBI.Traumatic brain injury is an urgent problem in medicine and healthcare in most countries, including Russia. This state of affairs is due to the widespread prevalence of this pathology, high levels of temporary disability, disability and mortality. Accordingly, TBI is objectively positioned as a serious socio-economic problem. For example, in the United States, the economic damage from TBI amounts to an average of $37.8 billion per year.